Multivariate data analysis - Hair Joseph F; Anderson Rolph E; Black William C; Tatham Ronald L (Delhi Pearson Education, 2005)
This revised edition presents strongly grounded in statistical techniques, but focusing on design, estimation, and interpretation. Here is also provided a firm understanding of the statistical and managerial principles so as to develop a comfort zone for
Keywords: Multivariate data analysis